Intolerance of uncertainty, curiosity, generalized anxiety disorder, and subjective happiness in the time of earthquakes in Turkiye - Yllmaz, Fatma Betul; Satlcl, Seydi Ahmet; Okur, Sinan; Kutuk, Hasan; Aktepe, Zahide Gul (TERMEDIA PUBLISHING HOUSE LTD, 2025)
BACKGROUND On February 6, 2023, a devastating earthquake disaster occurred in Ti rkiye, affecting millions. Mental health concerns were high due to people's exposure to loss and possible earthquakes. In these times, variables that predict individuals' mental health should be determined. The aim of this study was to investigate the relationship between intolerance of uncertainty, curiosity, generalized anxiety disorder, and subjective happiness using structural equation modeling. PARTICIPANTS AND PROCEDURE The research was conducted on Turkish individuals in 29 different cities in Ti rkiye. For the purpose of the research, data were collected from 345 participants (79.7% females, 20.3% males, age range = 18-61, Mage = 26.73 years). One hundred eighty nine of the participants were single (54.7%), 77 were married (22.4%), and the remaining 79 were in a relationship or engaged (22.9%). Additionally, it was found that 52 of the participants were parents (15.1%). Interms of socio-economic status, the majority fell into the middle-class category (n = 263, 76.2%). RESULTS It was found that intolerance to uncertainty predicted subjective happiness, and generalized anxiety disorder mediated this relationship. In addition, curiosity predicted subjective happiness, and generalized anxiety disorder mediated this relationship. CONCLUSIONS All the findings obtained in the research revealed the mental health problems experienced by individuals after the earthquake. This research on earthquakes and mental health makes important contributions to the field of psychology.
Keywords: curiosity; generalized anxiety disorder; intolerance of uncertainty; subjective happiness; earthquake; QUALITY-OF-LIFE; CLINICAL-TRIAL; MENTAL-HEALTH; SYMPTOMS; STRESS; ORIENTATION; RELIABILITY; ADAPTATION; DEPRESSION; DIAGNOSIS; Psychology